Death case detected with a new synthetic opioid protonitazene - Aksoy, Ufuk; Mutlu, Emre; Çoban, İsmail (The Bulletin of Legal Medicine, 2025)
The recent reemergence and increasing popularity of nitazenes, a new class of synthetic opioids belonging to the benzimidazole chemical class, has raised public health concerns. Development of these agents was discontinued in the 1950s because of their high abuse potential, but little is known about their pharmacokinetics and pharmacodynamics. These gaps in knowledge pose significant challenges to early detection and treatment of poisoning. Protonitazen is a potent new synthetic opioid in this class. Protonitazen is structurally different from synthetic opioids typically encountered in forensic work (e.g., fentanyl, heroin). In vitro pharmacological data suggest that this new opioid is similar in potency to other recently introduced “nitazen” opioids and is approximately three times more potent than fentanyl. The toxicity of protonitazen has not been adequately studied or reported, but the identification of recent cases of fatalities in drug users suggests that this synthetic opioid has the potential to cause widespread harm. This study aims to share a multiple drug poisoning case in which a new synthetic opioid was detected in biological samples, to provide information about protonitazen, a new synthetic opioid with a high lethal potential due to its efficacy and potency and which is important because it has a tendency to infiltrate the drug market in our country, to raise awareness about nitazens and to draw attention to the fact that toxicology laboratories should be alert against these substances.